UMP ranked 134th in Asia - Hazlina, Faizal (2019)
Universiti Malaysia Pahang (UMP) achieved a remarkable accomplishment when ranked at 134th spot in Asia in the recently released QS Asia University Rankings 2020.The continuous climb in five consecutive years also makes UMP as the first university in the Malaysian Technological University Network (MTUN) to place itself in the 150 best universities in Asia.UMP had climbed 54 spots this year from 188th last year.